An all-sky survey of circular polarization at 200 MHz - Lenc, E.; Murphy, T.; Lynch, Christene; Kaplan, D.; Zhang, S. (Oxford University Press, 2018)
We present results from the first all-sky radio survey in circular polarization. The survey uses the Murchison Widefield Array (MWA) to cover 30 900 sq deg, over declinations south of +30° and north of -86° centred at 200MHz (over a 169-231MHz band).We achieve a spatial resolution of ~3 arcmin and a typical sensitivity of 3.0mJy PSF-1over most of the survey region. We demonstrate a new leakage mitigation technique that reduces the leakage from total intensity into circular polarization by an order of magnitude. In a blind survey of the imaged region, we detect 14 pulsars in circular polarization above a 6s threshold. We also detect six transient sources associated with artificial satellites. A targeted survey of 2376 pulsars within the surveyed region yielded 33 detections above 4s. Looking specifically at pulsars previously detected at 200 MHz in total intensity, this represents a 35 per cent detection rate. We also conducted a targeted survey of 2400 known flare stars, this resulted in two tentative detections above 4s. A similar targeted search for 1506 known exoplanets in the field yielded no detections above 4s. The success of the survey suggests that similar surveys at longer wavelength bands and of deeper fields are warranted.